Access Networks 4th International Conference, AccessNets 2009, Hong Kong, China, November 1-3, 2009, Revised Selected Papers - Jun Hei, Xiao; Cheung, Lawrence (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the Fourth International Conference on Access Networks, AccessNets 2009, held in Hong Kong, China, in November 2009. The 11 revised full papers presented together with 8 invited papers were carefully reviewed and selected. The papers present original and fundamental research advances in the area of access networks, such as hybrid dynamic bandwidth and wavelength allocation algorithm, diversified applications in EPON, unsolicited grant services (UGS), mobile WiMAX network, FiWi networks, integrated PON-WiMAX networks, cognitive radio networks, efficient and dynamic spectrum sharing, cross-layer routing method for SCTP, and vectored DSL.